Evaluation of the effects of intra-arterial sugammadex and dexmedetomidine: an experimental study - Hancı,Volkan (2016)
Abstract Background: Intra-arterial injection of medications may cause acute and severe ischemia and result in morbidity and mortality. There is no information in the literature evaluating the arterial endothelial effects of sugammadex and dexmedetomidine. The hypothesis of our study is that sugammadex and dexmedetomidine will cause histological changes in arterial endothelial structure when administered intra-arterially. Methods: Rabbits were randomly divided into 4 groups. Group Control (n = 7); no intervention performed. Group Catheter (n = 7); a cannula inserted in the central artery of the ear, no medication was administered. Group Sugammadex (n = 7); rabbits were given 4 mg/kg sugammadex into the central artery of the ear, and Group Dexmedetomidine (n = 7); rabbits were given 1 µg/kg dexmedetomidine into the central artery of the ear. After 72 h, the ears were amputated and histologically investigated. Results: There was no significant difference found between the control and catheter groups in histological scores. The endothelial damage, elastic membrane and elastic fiber damage, smooth muscle hypertrophy and connective tissue increase scores in the dexmedetomidine and sugammadex groups were significantly higher than both the control and the catheter groups (p < 0.05). There was no significant difference found between the dexmedetomidine and sugammadex groups in histological scores. Conclusion: Administration of sugammadex and dexmedetomidine to rabbits by intra-arterial routes caused histological arterial damage. To understand the histological changes caused by sugammadex and dexmedetomidine more clearly, more experimental research is needed.